A kind of amine modified hierarchical structure photocatalytic material and its preparation method and application
Through amine modification of the hierarchical structure photocatalytic material, combined with TiO2@Na2Ti3O7 composite material and silver loading technology, the problem of difficulty in coordination of CO2 capture and reduction reactions is solved, the photocatalytic efficiency is significantly improved, and the efficient CO2 reduction effect is achieved.
Patent Information
- Application Number
- CN202411252621.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-09-09
AI Technical Summary
During the CO2 reduction photocatalysis process, the prior art is difficult to coordinate CO2 capture and reduction reactions, and the performance of the catalytic materials is insufficient, resulting in low catalytic efficiency.
The amine-modified hierarchical structure photocatalytic material was used to synthesize the TiO2@Na2Ti3O7 composite material, and the surface ethylenediamine modification and silver support were carried out. Silver acts as the activation site for CO2 and H2O adsorption, and cooperates with ethylenediamine to enhance CO2 capture; Na+ promotes charge separation and migration, and Ag acts as an electron trap to suppress charge reflux through the Schottky barrier, improving electron utilization.
The photocatalytic efficiency is significantly improved and has good application prospects in the field of CO2 capture and reduction. When the catalytic material is subjected to photocatalytic CO2 reduction test in pure water, the CH4 activity reaches 9.01 μmol/g/h.
Smart Images

Figure CN119237009B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to CO 2 The technical field of reducing photocatalytic materials is an amine-modified hierarchical structure photocatalytic material and a preparation method and application thereof. Background Art
[0002] CO 2 The conversion of CO into valuable value-added chemicals can contribute to the carbon circular economy. Photocatalytic technology directly utilizes solar energy without additional energy consumption. 2 During reduction, substrate and intermediate adsorption, charge transfer, etc. must be considered. 2 It is challenging to capture and reduce CO with excellent performance. As we all know, efficient photocatalytic reactions must have the advantages of strong light absorption and conversion ability, fast charge separation and migration, and rapid catalytic reaction. 2 The molecules have strong adsorption and activation capabilities, the photogenerated charges migrate quickly on the catalyst surface, and the intermediate products in the catalytic process are easily desorbed and transferred, which can accelerate the surface redox reaction and improve the catalytic conversion efficiency.
[0003] Focusing on the photocatalytic material system, it is required to have strong component adjustability and easy polarization of the bulk phase. 2 It is a research hotspot in the field of photocatalysis, with high element abundance and good chemical stability. 6 Octahedron is the basic structural unit, and the energy band is dominated by O 2p and Ti 3d orbitals, and the size and position are controllable. It is often difficult to have both a wide absorption range and high absorption intensity. Morphology control is a common method to enhance photocatalytic activity. Among the many morphologies, alkali metal titanates (M x TiO y ) has attracted attention due to its special layered stepped pore structure and fast charge separation and migration. It uses weak interlayer interactions to achieve "surfaceization" of the bulk phase, making heterogeneous atoms evenly distributed in the bulk phase of the material and inducing bulk polarization. 2 -M x TiO y The composite material is used in photocatalytic degradation, water splitting and hydrogen evolution, etc. The built-in electric field is used to drive the photogenerated charges to move in the opposite direction to the surface of the material and achieve good catalytic effects. 2 There are fewer restore applications.
[0004] Surface modification is an important way to improve the photocatalytic CO 2 One of the effective ways to reduce CO 2Strong adsorption on the surface of the material is a prerequisite for high reduction activity. Lack of adsorption strength will terminate the reaction process. Common surface modifications include Lewis acids / bases, metals, metal oxides, etc. Only a single modification often faces the problem of monotonous function. It is possible to construct synergistic sites and achieve CO 2 Efficient adsorption and activation.
[0005] Based on the above analysis, the following design ideas are proposed: synthesizing TiO with multiple structures 2 @Na 2 Ti 3 O 7 Composite materials with simultaneous surface ethylenediamine modification and silver loading. On the one hand, silver acts as a CO 2 and H 2 O adsorption activation sites and ethylenediamine synergistically enhance CO 2 Capture; on the other hand, Na + It promotes charge separation migration and orderly surface enrichment. Ag acts as an electron trap to inhibit charge reflux through Schottky barrier and improve electron utilization. Summary of the invention
[0006] The purpose of the present invention is to provide an amine-modified hierarchical structure photocatalytic material and a preparation method and application thereof, so as to solve the problems raised in the above background technology.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing an amine-modified hierarchical structure photocatalytic material, which is prepared by the following method:
[0009] S1. Add ethylene glycol to a round-bottom flask, then drop butyl titanate and mix evenly with ultrasound, reflux in an oil bath at 110-130°C for 0.8-1.5h, cool completely for standby use after the reaction is completed, wash with water and ethanol, and dry in a 55-65°C forced air drying oven to obtain a white powder;
[0010] S2, ultrasonically disperse the white powder obtained in step S1 into deionized water, then add ethylenediamine and continue ultrasonication to obtain a reaction solution, transfer the reaction solution to a reactor and react at 160-210° C. for 5.4-6.8 h, cool to room temperature after the reaction, wash, and vacuum dry at 45-70° C. for 10-16 h to obtain amine-modified protonated titanic acid (NH 2 -H 2 Ti 2 O 5 ·H 2 O);
[0011] S3, ultrasonically dissolving the protonated titanic acid and sodium hydroxide prepared in step S2 in deionized water, adding ethylene glycol, and continuing to add a silver nitrate solution with a concentration of 1 mol / L and ultrasonically dispersing until completely dispersed to obtain a mixed solution;
[0012] S4, adding the mixed solution obtained in step S3 into a reactor, reacting at 150-200° C. for 11-14 h, after the reaction is completed, washing, and vacuum drying at 50-70° C. overnight to obtain an amine-modified hierarchical structure photocatalytic material (NH 2 / TiO 2 @Na 2 Ti 3 O 7 -Ag).
[0013] Furthermore, in step S1, the volume ratio of ethylene glycol to butyl titanate is 40:1.
[0014] Furthermore, the volume ratio of butyl titanate in step S1 to deionized water and ethylenediamine in step S2 is 2:25:45, and the cleaning step in step S2 includes first cleaning three times with deionized water and then cleaning once with anhydrous ethanol.
[0015] Furthermore, in the step S3, the mass ratio of protonated titanic acid, sodium hydroxide and deionized water is 2:1:200, and the volume ratio of ethylene glycol, deionized water and silver nitrate in the step S2 is (1-3):1:(0.0005-0.005).
[0016] Furthermore, the cleaning step in step S4 includes first washing to the center with deionized water and then washing once with ethanol.
[0017] An amine modified hierarchical structure photocatalytic material is prepared by adopting the amine modified hierarchical structure photocatalytic material preparation method.
[0018] A method for preparing an amine-modified hierarchical structure photocatalytic material. The photocatalytic material prepared by the method or an amine-modified hierarchical structure photocatalytic material has the advantages of catalyzing CO 2 Application in the field.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention successfully synthesized TiO with multiple structures by thermal solvent method. 2 @Na 2 Ti 3 O 7 Composite materials, surface ethylenediamine modification and silver loading, on the one hand, silver acts as a CO 2 and H 2 O adsorption activation sites and ethylenediamine synergistically enhance CO2 Capture; on the other hand, Na + It promotes charge separation migration and orderly surface enrichment. Ag acts as an electron trap to inhibit charge reflux through Schottky barrier and improve electron utilization. The synergistic effect between the two greatly promotes the photocatalytic efficiency. 2 It has very good application prospects in the capture and reduction fields. When the amount of silver nitrate was 0.025 ml, the catalytic material photocatalyzed CO in pure water. 2 Reduction test, CH 4 The activity reached 9.01μmol / g / h. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a process flow chart of the present invention;
[0022] Figure 2 EG / H in step S3 of Example 1 of the present invention 2 SEM and EDX images of the solvothermal products when the O ratio is 20 / 20;
[0023] Figure 3 is EG / H in step S3 of Example 6 of the present invention. 2 SEM and EDX images of the solvothermal products when the O ratio is 30 / 10
[0024] Figure 4 The SEM and EDX images of the amine-modified hierarchical structure photocatalytic material in Example 1 of the present invention;
[0025] Figure 5 XRD and FT-IR images of Ag, NTN and NTN-Ag in Examples 1-4 of the present invention;
[0026] Figure 6 NTN and NTN-Ag in Example 1 of the present invention 0.025 XPS images of (a) survey, (b) Ti 2p, (c) O 1s, (d) Na 1s, (e) N 1s and (f) Ag 3d;
[0027] Figure 7 The photocatalytic CO of NTN and NTN-Ag composite materials in Examples 1-4 of the present invention 2 Reduction activity. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] See also Figures 1 to 7 , the present invention provides:
[0030] Example 1
[0031] A method for preparing an amine-modified hierarchical structure photocatalytic material comprises the following steps:
[0032] S1. Add 80 ml of ethylene glycol into a round-bottom flask, then drop 2 ml of butyl titanate and mix evenly with ultrasound, reflux in an oil bath at 120°C for 1 hour, cool completely for standby use after the reaction is completed, wash with water and ethanol, and dry in a 60°C forced air drying oven to obtain a white powder;
[0033] S2, ultrasonically dispersing the white powder obtained in step S1 into 25 ml of deionized water, then adding 45 ml of ethylenediamine and continuing ultrasonication to obtain a reaction solution, transferring the reaction solution to a 100 ml reactor and reacting at 180° C. for 6 h, cooling to room temperature after the reaction, washing three times with deionized water and once with ethanol, and vacuum drying at 60° C. for 12 h to obtain amine-modified protonated titanic acid;
[0034] S3, ultrasonically dissolving 0.2 g of the protonated titanic acid and 0.1 g of sodium hydroxide prepared in step S2 in 20 ml of deionized water, adding 20 ml of ethylene glycol, and then adding 0.025 ml of a 1 mol / L silver nitrate solution and ultrasonically dispersing until completely dispersed to obtain a mixed solution;
[0035] S4, adding the mixed solution obtained in step S3 into a 100 ml reactor, reacting at 180° C. for 12 h, after the reaction is completed, washing with deionized water until neutral, washing once with ethanol, and vacuum drying at 60° C. overnight to obtain an amine-modified hierarchical structure photocatalytic material (NH 2 / TiO 2 @Na 2 Ti 3 O 7 -Ag), referred to as NTN-Ag, for example NTN-Ag 0.025 , adding AgNO 3 The volume is 0.025mL.
[0036] Example 2
[0037] A method for preparing an amine-modified hierarchical structure photocatalytic material comprises the following steps:
[0038] S1. Add 80 ml of ethylene glycol into a round-bottom flask, then drop 2 ml of butyl titanate and mix evenly with ultrasound, reflux in an oil bath at 120°C for 1 hour, cool completely for standby use after the reaction is completed, wash with water and ethanol, and dry in a 60°C forced air drying oven to obtain a white powder;
[0039] S2, ultrasonically dispersing the white powder obtained in step S1 into 25 ml of deionized water, then adding 45 ml of ethylenediamine and continuing ultrasonication to obtain a reaction solution, transferring the reaction solution to a 100 ml reactor and reacting at 180° C. for 6 h, cooling to room temperature after the reaction, washing three times with deionized water and once with ethanol, and vacuum drying at 60° C. for 12 h to obtain amine-modified protonated titanic acid;
[0040] S3, ultrasonically dissolving 0.2 g of the protonated titanic acid and 0.1 g of sodium hydroxide prepared in step S2 in 20 ml of deionized water, adding 20 ml of ethylene glycol, and then adding 0.01 ml of a 1 mol / L silver nitrate solution and ultrasonically dispersing the solution until the solution is completely dispersed to obtain a mixed solution;
[0041] S4, adding the mixed solution obtained in step S3 into a 100 ml reactor, reacting at 180°C for 12 hours, after the reaction is completed, washing with deionized water until neutral, washing once with ethanol, and vacuum drying at 60°C overnight to obtain NTN-Ag 0.01 .
[0042] Example 3
[0043] A method for preparing an amine-modified hierarchical structure photocatalytic material comprises the following steps:
[0044] S1. Add 80 ml of ethylene glycol into a round-bottom flask, then drop 2 ml of butyl titanate and mix evenly with ultrasound, reflux in an oil bath at 120°C for 1 hour, cool completely for standby use after the reaction is completed, wash with water and ethanol, and dry in a 60°C forced air drying oven to obtain a white powder;
[0045] S2, ultrasonically dispersing the white powder obtained in step S1 into 25 ml of deionized water, then adding 45 ml of ethylenediamine and continuing ultrasonication to obtain a reaction solution, transferring the reaction solution to a 100 ml reactor and reacting at 180° C. for 6 h, cooling to room temperature after the reaction, washing three times with deionized water and once with ethanol, and vacuum drying at 60° C. for 12 h to obtain amine-modified protonated titanic acid;
[0046] S3, ultrasonically dissolving 0.2 g of the protonated titanic acid and 0.1 g of sodium hydroxide prepared in step S2 in 20 ml of deionized water, adding 20 ml of ethylene glycol, and then adding 0.05 ml of a 1 mol / L silver nitrate solution and ultrasonically dispersing until completely dispersed to obtain a mixed solution;
[0047] S4, adding the mixed solution obtained in step S3 into a 100 ml reactor, reacting at 180°C for 12 hours, after the reaction is completed, washing with deionized water until neutral, washing once with ethanol, and vacuum drying at 60°C overnight to obtain NTN-Ag 0.05 .
[0048] Example 4
[0049] A method for preparing an amine-modified hierarchical structure photocatalytic material comprises the following steps:
[0050] S1. Add 80 ml of ethylene glycol into a round-bottom flask, then drop 2 ml of butyl titanate and mix evenly with ultrasound, reflux in an oil bath at 120°C for 1 hour, cool completely for standby use after the reaction is completed, wash with water and ethanol, and dry in a 60°C forced air drying oven to obtain a white powder;
[0051] S2, ultrasonically dispersing the white powder obtained in step S1 into 25 ml of deionized water, then adding 45 ml of ethylenediamine and continuing ultrasonication to obtain a reaction solution, transferring the reaction solution to a 100 ml reactor and reacting at 180° C. for 6 h, cooling to room temperature after the reaction, washing three times with deionized water and once with ethanol, and vacuum drying at 60° C. for 12 h to obtain amine-modified protonated titanic acid;
[0052] S3, ultrasonically dissolving 0.2 g of the protonated titanic acid and 0.1 g of sodium hydroxide prepared in step S2 in 20 ml of deionized water, adding 20 ml of ethylene glycol, and then adding 0.1 ml of a 1 mol / L silver nitrate solution and ultrasonically dispersing the solution until the solution is completely dispersed to obtain a mixed solution;
[0053] S4, adding the mixed solution obtained in step S3 into a 100 ml reactor, reacting at 180°C for 12 hours, after the reaction is completed, washing with deionized water until neutral, washing once with ethanol, and vacuum drying at 60°C overnight to obtain NTN-Ag 0.1 .
[0054] In step S3 of Examples 1-4, the ratio of ethylene glycol to deionized water is 20:20 (EG / H 2 O ratio is 20 / 20);
[0055] Example 5
[0056] A method for preparing an amine-modified hierarchical structure photocatalytic material comprises the following steps:
[0057] S1. Add 80 ml of ethylene glycol into a round-bottom flask, then drop 2 ml of butyl titanate and mix evenly with ultrasound, reflux in an oil bath at 110°C for 0.8 h, cool completely for later use after the reaction is completed, wash with water and ethanol, and dry in a 55°C forced air drying oven to obtain a white powder;
[0058] S2, ultrasonically dispersing the white powder obtained in step S1 into 25 ml of deionized water, then adding 45 ml of ethylenediamine and continuing ultrasonication to obtain a reaction solution, transferring the reaction solution to a 100 ml reactor and reacting at 160° C. for 5.4 h, cooling to room temperature after the reaction, washing three times with deionized water and once with ethanol, and vacuum drying at 45° C. for 10 h to obtain amine-modified protonated titanic acid;
[0059] S3, ultrasonically dissolving 0.2 g of the protonated titanic acid and 0.1 g of sodium hydroxide prepared in step S2 in 20 ml of deionized water, adding 25 ml of ethylene glycol, and then adding 0.025 ml of a 1 mol / L silver nitrate solution and ultrasonically dispersing until completely dispersed to obtain a mixed solution;
[0060] S4, adding the mixed solution obtained in step S3 into a 100 ml reactor, reacting at 150° C. for 11 h, after the reaction is completed, washing with deionized water until neutral, washing once with ethanol, and vacuum drying at 50° C. overnight to obtain NTN-Ag 0.025 .
[0061] Example 6
[0062] A method for preparing an amine-modified hierarchical structure photocatalytic material comprises the following steps:
[0063] S1. Add 80 ml of ethylene glycol into a round-bottom flask, then drop 2 ml of butyl titanate and mix evenly with ultrasound, reflux in an oil bath at 130°C for 1.5 h, cool completely for later use after the reaction is completed, wash with water and ethanol, and dry in a 65°C forced air drying oven to obtain a white powder;
[0064] S2, ultrasonically dispersing the white powder obtained in step S1 into 25 ml of deionized water, then adding 45 ml of ethylenediamine and continuing ultrasonication to obtain a reaction solution, transferring the reaction solution to a 100 ml reactor and reacting at 210° C. for 6.8 h, cooling to room temperature after the reaction, washing three times with deionized water and once with ethanol, and vacuum drying at 70° C. for 16 h to obtain amine-modified protonated titanic acid;
[0065] S3, ultrasonically dissolving 0.2 g of the protonated titanic acid and 0.1 g of sodium hydroxide prepared in step S2 in 10 ml of deionized water, adding 30 ml of ethylene glycol, and then adding 0.025 ml of a 1 mol / L silver nitrate solution and ultrasonically dispersing until completely dispersed to obtain a mixed solution;
[0066] S4, add the mixed solution obtained in step S3 into a 100 ml reactor, react at 200°C for 14 hours, and after the reaction is completed, wash with deionized water until neutral, wash once with ethanol, and dry in vacuum at 70°C overnight to obtain NTN-Ag 0.025 .
[0067] Sample characterization methods
[0068] X-ray powder diffraction (XRD) was performed on an Ultima IV diffractometer with a scanning range of 20-80°, 40 kV, 40 mA, and 10° / min. Morphological observation and elemental mapping analysis (SEM and EDX) were performed on a Gemini SEM 300. The element types, binding energy, and valence band of the materials were determined by X-ray photoelectron spectroscopy (XPS, Thermo Scientific K-Alpha+). The ultraviolet-visible diffuse reflectance spectra (UV-DRS) of the materials were determined using a Shimadzu UV2550 spectrophotometer with a wavelength range of 200-800 nm. The CHI 760E electrochemical workstation and a three-electrode system (Pt counter electrode, Hg / Hg 2 Cl 2 Or Ag / AgCl reference electrode, FTO working electrode) were used to measure the transient photocurrent response (TPC), photocurrent (PC), and electrochemical impedance spectroscopy (EIS). The TPC and PC test solutions were 0.2 M sodium sulfate solution, and the EIS test solution was a 5 mM mixed solution of potassium ferrocyanide, potassium ferrocyanide and potassium chloride. The Fourier transform infrared (FT-IR) spectrum of the sample was measured on an infrared spectrometer (Nicolet iS10) to analyze the amino groups on the surface of the material, with potassium bromide as the dilution.
[0069] Photocatalytic CO 2 Restoration Method
[0070] The reduction test was carried out in a quartz reactor with a volume of about 200 mL. 50 mg of the sample was dissolved in 1 mL of deionized water, and after complete ultrasonic dispersion, it was evenly deposited on a glass culture dish with a diameter of 3.5 cm. At the same time, 10 ml of deionized water was added to the bottom of the reactor as a water vapor source. The culture dish was placed at the bottom of the reactor to photocatalyze CO 2 The reduction experiment was carried out under simulated sunlight, and high-purity CO was introduced into the bottom of the reactor before turning on the light. 2 Bubble for 0.5h to remove dissolved oxygen and air to produce pure CO 2 The temperature of the reduction system was maintained at 25°C by circulating condensed water, and a 300 W xenon lamp was used as the light source (CEL-HXF300, CEAULIGHT Beijing). After the light was turned on, 1 mL of gas was drawn with a syringe every hour and injected into a gas chromatograph (GC-7900, CEAULIGHT Beijing) for analysis using a FID detector.
[0071] Characterization results
[0072] Reference Figure 2 (SEM and EDX images of the samples), in EG / H 2O ratio of 20 / 20 to obtain sodium titanate nanosheets, further increasing the EG content (refer to Figure 3 ), give full play to EG and Na + The chelation and support effect successfully + Introducing the interlayer, again + OH - The interaction between Na and EG results in a 0D / 1D@2D structure: + Entering the interlayer promotes the interaction and coordination between EG and Ti-O surface, and OH - The -NH 3 + / H + , charge imbalance forms defects, nanosheets curl, and the chelation effect of EG also causes nanosheets to aggregate. When these three interact, OH - Attack Layer-NH 3 + / H + The inner layer is exposed, and EG forms a complex with the surface of the material while stabilizing Na + , which will support the surface nanosheet structure to remain unchanged and form Na 2 Ti 3 O 7 Mutually.
[0073] EG / H 2 SEM and EDX images of the hot solvent product when the O ratio is 30 / 10
[0074] Since excessive Na+ can cause serious charge recombination, which is counterproductive, the EG / H 2 O ratio of 20 / 20 for subsequent synthesis studies, Figure 4 NTN-Ag 0.025 SEM and EDX images; Under the combined action of EG and NaOH, NH 2 -H 2 Ti 2 O 5 ·H 2 O still has a 0D-1D@2D structure after surface reconstruction. The whole structure is rod-shaped, and the surface is stacked nanosheets. The appearance of Na element in EDX confirms the successful synthesis of sodium titanate phase. Silver reduction is synchronized with the formation of sodium titanate nanosheets. 0.025 In the sample, a large number of silver particles can be observed scattered on the surface of the nanosheets, and the silver nanoparticle signal in EDX is very obvious.
[0075] Figure 5 (a) is the XRD spectrum of the product collected when silver reduction was performed alone without adding protonated titanic acid. 0XRD (JCPDS No.1-1167) of EG / H 2 O system can be used for Ag 0 Load; Figure 5 (b) is EG / H 2 O ratio of 20 / 20 NTN, also with brookite TiO 2 (JCPDS No.18-875) and Na 2 Ti 3 O 7 (JCPDS No.31-1329) and successfully constructed TiO 2 @Na 2 Ti 3 O 7 , the diffraction angles of 37.8° and 43.8° are the (111) and (200) crystal planes of silver; Figure 5 In (c), the diffraction peak intensity increases with the increase of silver loading; Figure 5 (d) NTN and NTN-Ag 0.025 The FT-IR spectrum shows that the -1 1630cm -1 There are two obvious absorption peaks at , the former corresponds to the stretching vibration of NH, and the latter corresponds to the bending vibration of NH, indicating that the surface amine functionalization modification was successfully carried out.
[0076] XPS is often used to analyze the elemental composition and chemical state of material surfaces; Figure 6 (a) NTN-Ag 0.025 It shows signals of five elements: Ti, O, Na, N and Ag; Figure 6 The binding energies of 458 and 464 eV in (b) are respectively attributed to Ti 4+ 2p 3 / 2 and Ti 2p 1 / 2 , while the satellite peak at 460 eV belongs to Ti 3+ ; Figure 6 The binding energies around 530 and 531 eV in (c) correspond to lattice oxygen (Ti-O) and surface hydroxyl groups (OH); Figure 6 The single peak of Na 1s in (d) is around 1071 eV; Figure 6 The XPS spectrum of N1s in (e) has two peaks at about 399 and 400 eV, corresponding to -NH 2 and NH diffraction peaks, again indicating successful surface amine functionalization; Figure 6 There are two prominent peaks in (f), which are Ag 3d 5 / 2 (367.5eV) and 3d 3 / 2(373.5eV), a difference of 6eV, indicating that it is silver; compared with NTN, NTN-Ag 0.025 The binding energies of Ti 2p, O 1s, and Na 1s shifted toward higher binding energies, indicating that the Ag loading 0 The electronic environment of the carrier is changed, and the strong interaction between Ag and NTN carrier induces electron transfer and localization on Ag; at the same time, the charge density of ethylenediamine increases, which is also more conducive to the adsorption of carbon dioxide.
[0077] In pure water system, CH 4 The photocatalytic CO and CO yields were evaluated. 2 The reduction activity of the four NTN-Ag prepared in Examples 1-4 was evaluated. Figure 7 As shown, the activity of amine-modified protonated titanic acid is very low, CH 4 The production rates of CH 4 The electron selectivity of NTN-Ag is about 96%. After the surface is loaded with Ag, the activity is greatly improved; 0.025 CH 4 The activity was 9.01 μmol / g / h, which was nearly 64 times higher than that of the monomer. At the same time, the CO activity was also greatly improved. The activity decreased with further increase in loading. Compared with CH 4 and CO activity ratio, it can be seen that the addition of Ag further increased the CH 4 Selectivity, Ag and surface amino groups work together to inhibit the desorption of *CO to form CO, and continue to add hydrogen to CH 4 Conversion.
[0078] The present invention uses a solvothermal method to achieve surface reconstruction of amine-modified protonated titanic acid under the combined action of sodium hydroxide and ethylene glycol, and successfully obtains a homogeneous NH with a 0D / 1D@2D structure. 2 -TiO 2 @Na 2 Ti 3 O 7 The catalytic carrier (the core is brookite phase) was successfully loaded with Ag nanoparticles simultaneously; in the photocatalytic CO 2 In the reduction test, the optimal loading amount of Ag was 0.025 mmol, CH 4 The activity is as high as 9.01μmol / g / h; the photoelectric test results reveal that the synergistic adsorption of ethylenediamine and silver is effective in improving CO 2 The reduction performance of the material plays a decisive role; although ethylenediamine improves the surface CO 2 However, due to the lack of effective charge transfer, most of the adsorption sites cannot be further activated and reduce CO 2, are all invalid active sites with low catalytic efficiency; the loading of silver not only improves the photoelectric properties of the material, but also adsorbs and activates CO with ethylenediamine 2 The hydrogenation reduction is promoted, so that the adsorption performance of ethylenediamine can be fully exerted. In the present invention, sodium titanate is prepared by sodium hydroxide and ethylene glycol, and the photocatalytic efficiency is greatly improved through the synergistic effect of surface amine modification and Ag loading.
[0079] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an amine-modified hierarchical structure photocatalytic material, characterized in that: Prepared by the following method: S1. Add ethylene glycol to a round-bottom flask, then drop butyl titanate and mix evenly with ultrasound, reflux in an oil bath at 110-130°C for 0.8-1.5h, cool completely for standby use after the reaction is completed, wash with water and ethanol, and dry in a 55-65°C forced air drying oven to obtain a white powder; S2, ultrasonically dispersing the white powder obtained in step S1 into deionized water, then adding ethylenediamine and continuing ultrasonication to obtain a reaction solution, transferring the reaction solution to a reactor and reacting at 160-210° C. for 5.4-6.8 h, cooling to room temperature after the reaction, washing, and vacuum drying at 45-70° C. for 10-16 h to obtain amine-modified protonated titanic acid NH2-H2Ti2O5·H2O; S3, ultrasonically dissolving the amine-modified protonated titanic acid and sodium hydroxide prepared in step S2 in deionized water, adding ethylene glycol, and continuing to add a silver nitrate solution with a concentration of 1 mol / L and ultrasonically dispersing until completely dispersed to obtain a mixed solution; In step S3, the mass ratio of amine-modified protonated titanic acid, sodium hydroxide and deionized water is 2:1:200; S4. Add the mixed solution obtained in step S3 into a reactor, react at 150-200° C. for 11-14 hours, and after the reaction is completed, wash and vacuum dry at 50-70° C. overnight to obtain an amine-modified hierarchical structure photocatalytic material NH2 / TiO2@Na2Ti3O7-Ag.
2. The method for preparing the amine-modified hierarchical structure photocatalytic material according to claim 1, characterized in that: In step S1, the volume ratio of ethylene glycol to butyl titanate is 40:
1.
3. The method for preparing the amine-modified hierarchical structure photocatalytic material according to claim 1, characterized in that: The volume ratio of butyl titanate in step S1 to deionized water and ethylenediamine in step S2 is 2:25:45, and the cleaning step in step S2 includes first cleaning three times with deionized water and then cleaning once with anhydrous ethanol.
4. The method for preparing the amine-modified hierarchical structure photocatalytic material according to claim 1, characterized in that: In step S3, the volume ratio of ethylene glycol to deionized water and silver nitrate is (1-3):1:(0.0005-0.005).
5. The method for preparing the amine-modified hierarchical structure photocatalytic material according to claim 1, characterized in that: The cleaning step in step S4 includes first washing with deionized water until it becomes neutral, and then washing once with ethanol.
6. An amine-modified hierarchical structure photocatalytic material, characterized in that: The photocatalytic material is prepared by the method for preparing the amine-modified hierarchical structure photocatalytic material as described in any one of claims 1 to 5.
7. Use of the photocatalytic material prepared by the method for preparing the amine-modified hierarchical structure photocatalytic material according to any one of claims 1 to 5 or the amine-modified hierarchical structure photocatalytic material according to claim 6 in the field of catalyzing CO2.
Citation Information
Patent Citations
Preparation method and use of silver-supported titanium dioxide photocatalyst
CN109967074A
Preparation method of anatase type nano titanium dioxide microspheres
CN111994950A